The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1186/1471-2229-13-54
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of tolerance to Boron toxicity in the legume Medicago truncatula

Abstract: BackgroundMedicago truncatula Gaertn. (barrel medic) is cultivated as a pasture legume for its high protein content and ability to improve soils through nitrogen fixation. Toxic concentrations of the micronutrient Boron (B) in agricultural soils hamper the production of cereal and leguminous crops. In cereals, the genetic analysis of B tolerance has led to the development of molecular selection tools to introgress and maintain the B tolerance trait in breeding lines. There is a comparable need for selection to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…The QTL region identified in this study is accurate and confirms the single locus identified in a previous study of B tolerance in lentil (Kaur et al., ). This finding is consistent with the outcomes of studies of B tolerance in other legume species such as pea (Sudheesh et al., ) and Medicago truncatula (Bogacki, Peck, Nair, Howie, & Oldach, ), which also reported single‐gene models. Using the dense genetic map developed, a more closely linked marker (Lc_0002525) was found for this B tolerance gene as compared to the markers identified from ILL2024 × ‘Cassab’.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The QTL region identified in this study is accurate and confirms the single locus identified in a previous study of B tolerance in lentil (Kaur et al., ). This finding is consistent with the outcomes of studies of B tolerance in other legume species such as pea (Sudheesh et al., ) and Medicago truncatula (Bogacki, Peck, Nair, Howie, & Oldach, ), which also reported single‐gene models. Using the dense genetic map developed, a more closely linked marker (Lc_0002525) was found for this B tolerance gene as compared to the markers identified from ILL2024 × ‘Cassab’.…”
Section: Discussionsupporting
confidence: 90%
“…The QTL region identified in this study is accurate and confirms the single locus identified in a previous study of B tolerance in lentil (Kaur et al, 2014). This finding is consistent with the outcomes of studies of B tolerance in other legume species such as pea and Medicago truncatula (Bogacki, Peck, Nair, Howie, & Oldach, 2013), which also reported single-gene models.…”
Section: Genetic Mapping Qtl Analysis and Marker Validationsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies in A. thaliana and M. truncatula have identified genes for efflux-type B transporters and members of the MIP family as controlling B toxicity tolerance [54,55,56,57]. The majority of known B tolerance-related genes described in model legume M. truncatula were shown to be present in the Cassab-derived transcriptome, validating integrated approach for large-scale identification of candidate genes for a given biological process.…”
Section: Discussionmentioning
confidence: 91%
“…To identify the candidate genes associated with tolerance to B toxicity [54,55,56,57] and time to flowering [58,59] in lentil, a text-based search of the Cassab transcriptome BLAST analysis data (against M. truncatula CDS, Nr and UniRef100) was performed. Two SNP-based linkage maps [38,39] which were used to precisely map QTLs for B toxicity tolerance and time to flowering were selected in this study.…”
Section: Methodsmentioning
confidence: 99%